The book of Lamentations : a meditation and translation - Slavitt, David R., 1935- (Johns Hopkins University Press, 2001)
More than a structural or mnemonic device, Slavitt argues, the acrostics are ""a serious assertion that the language itself is speaking, that the speech is inspired, and that there is, beyond all the disaster and pain the book recounts, an intricacy and an orderly coherence.""